Active CFRP-based confinement strategies for RC columns with rectangular cross sections - Agante, Marta A. B. (2017)
FRP wrapping is a strengthening technique for RC columns mostly used when a significant confinement increase is required. This technique is extremely effective in the case of circular cross-sections, but of marginally effectiveness for rectangular cross-sections columns. The use of post-tensioned CFRP jackets was an attempt to improve the confinement effectiveness for rectangular RC columns, but the level of success has been quite limited. This paper analyzes the viability of using an expansive resin to introduce some level of post-tension in CFRP jacket. In a first step, the optimal percentage of water added to trigger the resin expansion was analyzed. Using the obtained optimal value of water, the influence on the level of jacket post-tension of the width of the gap between the concrete surface and the CFRP jacket was investigated, and its timedependent sensitivity was assessed. Finally, the compression behaviour of specimens confined with this technique was assessed by performing experimental tests. The obtained results revealed that the adopted expansive resin is not an effective technique to assure high levels of post-tension in CFRP jackets for the concrete confinement.